Solution growth of peony-like copper hydroxyl-phosphate (Cu2(OH)PO4) flowers on Cu foil and their photocatalytic activity under visible light. (15th June 2016) - Yang, Siyuan; Xu, Kejia; Wang, Hongjuan; Yu, Hao; Zhang, Shanqing; Peng, Feng
Abstract: Novel self-assemble peony-like three-dimensional (3D) copper hydroxyl phosphate (Cu2 (OH)PO4 ) was synthesized on the copper foil by a solution-growth method. The self-aggregate peony-like 3D Cu2 (OH)PO4 flowers with the diameter size up to 10–20 μm were composed of hundreds of anisotropic cross-linking petals with several hundred nanometers wide and 110–170 nm thick. After the morphology and structure of these Cu2 (OH)PO4 flowers were characterized by transmission electron microscope and scanning electron microscope, the possible growth process of Cu2 (OH)PO4 flowers was proposed. The relationship between the shape of Cu2 (OH)PO4 nanostructure and photocatalytic activity under visible light irradiation was also investigated. The results indicated that a thin petal and high content of Cu2 (OH)PO4 flowers film on the copper substrate proved more convenient for extending their absorption edge to the visible light region, as well as giving a better photocatalytic performance. Graphical abstract: Novel self-assemble peony-like three-dimensional (3D) copper hydroxyl-phosphate (Cu2 (OH)PO4 ) were synthesized on the copper foil by a solution-growth method. The synthesized materials as a monolithic photocatalyst exhibited an effective photodecomposition to methylene blue (MB) under visible light irradiation. Highlights: Peony-like 3-dimensional copper hydroxyl phosphates are self-assembled on Cu foil. The growth mechanism of copper hydroxyl phosphate flowers is proposed. The as-designed nanomaterials can be used as a monolithic photocatalyst. This nanocomposites show good optical-electrical and photocatalytic properties.